Nonpermissivity of human peripheral blood lymphocytes to adenovirus type 2 infection. - Horvath, J (1988)
The capacity of freshly explanted human peripheral blood lymphocytes (PBL) to support the replication of human adenovirus type 2 (Ad2) was investigated. Unlike other types of human cells, PBL were found to be highly nonpermissive. Ad2 adsorbed 30 to 40% of both T and non-T cells. Virus uncoating was very slow and inefficient, resulting in a 40-fold reduction compared with HEp-2 cells. On a population basis, viral DNA synthesis was reduced 460-fold and infectious virus production was reduced 10(6)-fold. Only 0.35% of PBL produced infectious centers, yielding 0.8 PFU per infected cell. Phytohemagglutinin stimulation increased DNA synthesis 23-fold, infectious centers 11-fold, and virus yield 14-fold. We conclude that resting human PBL are highly nonpermissive to Ad2 infection and that phytohemagglutinin can only marginally lift this nonpermissiveness.